Endemic stability - a veterinary idea applied to human public health - Coleman, P.G.; Perry, Brian D.; Woolhouse, Mark E.J. (Elsevier, 2001)
Endemic stability is an epidemiological state of a population, in which clinical disease is scarce despite high level of infection. The notion was developed to describe patterns of tick-borne disease in cattle. However, we propose a general, nodes of endemic stability that is applicable to a broader range of diseases that are important in public health, including malaria, rubella, and mumps. We postulate that endemic stability requires only that (1) the probability, or severity, of clinical disease after infection increases with age, and (2) after one infection, the probability that subsequent infections result in disease is reduced. We present these criteria in simple mathematical terms. Our hypothesis predicts that partial disease control activities might, under certain circumstances, lead to an increase in disease incidence. We discuss the implications, for public health interventions.